A strategic model for evaluating energy efficient ICT infrastructures for sustainable environment - Masud, Mosharrof Hussain; Abdul Malik, Noreha (INSInet Publications, 2012)
Information and Communication Technology (ICT) is one of the fast growing industries that facilitate many latest services to the users and therefore, the number of users is increasing rapidly. The increment of the number of users is proportional to the ICT infrastructures. ICT infrastructures produce numerous environmental pollutions during its production and disposal. The usage and its life cycle produce hazardous substances that need to be addressed in efficient and green ways. In this regards, this paper evaluates the ICT infrastructures and its environmental impacts with carbon footprint. Energy consumption scenario is drawn for different ICT sectors that need to be minimized in certain level. Therefore, a strategic model is proposed to adopt green computing by all level of users from an individual to the authorized bodies including government. Awareness is the key influence for an individual that motivates the society and leads the authorized bodies to take the strategies towards green ICT advancements. The survey results showed that ICT users are becoming more concerned on green computing towards sustainable environment.